2018
DOI: 10.1037/dhe0000042
|View full text |Cite
|
Sign up to set email alerts
|

Older women, deeper learning, and greater satisfaction at university: Age and gender predict university students’ learning approach and degree satisfaction.

Abstract: The present study explored the interactive effect of age and gender in predicting surface and deep learning approaches. It also investigated how these variables related to degree satisfaction. Participants were 983 undergraduate students at a large public Australian university. They completed a research survey either online or in hardcopy. Consistent with previous research, age was a positive predictor of both surface and deep learning. However, gender moderated this age effect in the case of deep learning: Ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 52 publications
9
55
0
7
Order By: Relevance
“…Nor has the role of the gender variable been considered in this model, which previous research has proved to have an effect (Stöber, 2004; Rubin et al, 2016). For future research, some of these instruments should be revalidated to ensure structural adequacy and factorial invariance as a preliminary step to their use, given that some inconsistencies have been found in the results, such as the low reliability of the Scale of Spirituality (Resilience) in this university sample.…”
Section: Discussionmentioning
confidence: 99%
“…Nor has the role of the gender variable been considered in this model, which previous research has proved to have an effect (Stöber, 2004; Rubin et al, 2016). For future research, some of these instruments should be revalidated to ensure structural adequacy and factorial invariance as a preliminary step to their use, given that some inconsistencies have been found in the results, such as the low reliability of the Scale of Spirituality (Resilience) in this university sample.…”
Section: Discussionmentioning
confidence: 99%
“…Older women can also provide more intrinsic motivations for study (McCune et al, 2010). Recent research has linked these factors, finding that older female students more often have a deep learning approach than younger females or men of any age (Rubin, Scevak et al, 2016). …”
Section: Impact Of Gendermentioning
confidence: 99%
“…He claimed passing courses was 'no problem', although in some cases his grades indicated that he only just passed. This difference in attitude may be related to gender as mature female students have a deeper approach to learning (Rubin, Scevak et al, 2016) and are more likely to attribute any difficulties they experience in HE to themselves (O'Shea, 2014). For David, passing may have been the main goal.…”
Section: Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations